Direct Evidence of Reduction of Cloud Water after Spreading Diatomite Particles in Stratus Clouds in Beijing, China - Qiang Zhang; Mengyu Huang; Xuexi Tie; Xincheng Ma (Advances in Meteorology)
Artificial weather modification experiments have been intensively practiced in many years over China, and some progresses have been made, including more methodologies and advanced instruments. However, a challenge question still remains for providing convincing scientific evidence during these practices and experiments. This is a very difficult scientific issue, which is related to complicated cloud physical science, such as to accurately predict the large natural variability of cloud formation and precipitation. In this study, we report a clear evidence that the cloud water is reduced after spreading diatomite particles in stratus clouds during a field experiment in Beijing, China. The analysis shows that the diatomite particles (15–20 μm in radius) are large and have strong hygroscopic property (absorbing cloud water). As a result, during the experiment, spreading large diatomite particles lead to downward motion (producing more stable atmospheric condition) and reduction of cloud water. It is noted that due to lacks of instruments, this designed experiment only can provide a qualitative result (such as photo evidence), and no quantitative result can be drawn from this experiment.